The Red Spot Collection of the Main Library, Universiti Malaya - Lee, A. (University of Malaya Library, 1984)
The Red Spot collection of the University of Malaya Library is housed in the Institute of Post Graduate Studies and held books that lecturers have recommendated for short term reference. These are books on students' recommended reading list. The Red Spot collection hold 9,943 titles with a total volume of 25,379 items. Monographs form the major portion of the collection followed by photocpy of articles and final year academic exercises.